A model of brand switching by lead users of high-tech capital equipment. (1st January 2011) - Al-Kwifi, Sam O.; McNaughton, Rod B.
This study investigates the antecedents of brand switching by lead users of high-tech capital equipment. In markets for capital equipment, the incumbent is usually assumed to have an advantage because of high switching costs. However, much of the research on brand switching focuses on mass-market consumers of competitive products, where switching barriers are manageable. A model of the factors behind brand switching for capital equipment is developed and tested with data gathered by a survey of research centres around the world that use magnetic resonance imaging (MRI) equipment. The results confirm the expectation that lead users are willing to overcome high switching barriers to obtain a new technology when it is essential to renew organisational capabilities that are important to sustaining their competitive advantage. The decision to replace high-tech capital equipment is primarily influenced by the features and capabilities associated with the new product.